Purification and Characterization of Glucose-6-Phosphate Dehydrogenase from Camel Liver. (24th December 2014) - Ibrahim, Mahmoud A.; Ghazy, Abdel-Hady M.; Salem, Ahmed M. H.; Ghazy, Mohamed A.; Abdel-Monsef, Mohamed M.
Abstract : Glucose-6-phosphate dehydrogenase from camel liver was purified to homogeneity by ammonium sulfate precipitation and a combination of DEAE-cellulose, Sephacryl S-300 gel filtration, and 2′, 5′ ADP Sepharose 4B affinity chromatography columns. The specific activity of camel liver G6PD is increased to 1.80438 units/mg proteins with 63-fold purification. It turned out to be homogenous on both native PAGE and 12% SDS PAGE, with a molecular weight of 64 kDa. The molecular weight of the native form of camel liver G6PD was determined to be 194 kDa by gel filtration indicating a trimeric protein. The K m value was found to be 0.081 mM of NADP + . Camel liver G6PD displayed its optimum activity at pH 7.8 with an isoelectric point ( p I) of pH 6.6–6.8. The divalent cations MgCl2, MnCl2, and CoCl2 act as activators; on the other hand, CaCl2 and NiCl2 act as moderate inhibitors, while FeCl2, CuCl2, and ZnCl2 are potent inhibitors of camel liver G6PD activity. NADPH inhibited camel liver G6PD competitively with K i value of 0.035 mM. One binding site was deduced for NADPH on the enzyme molecule. This study presents a simple and reproducible purification procedure of G6PD from the camel liver.